F07 Expanding the response scale of the uhdrs total functional assessment: a pilot study. (16th November 2010) - Ho, A K; Barker, R A; Swain, R; O'Keefe, D
Abstract : Background: Although the twenty-five item UHDRS Total Functional Assessment (TFA) covers a wide range of aspects of daily living, its use as a functional assessment instrument for Huntington's disease (HD) is limited. The TFA uses a binary response scale, and is therefore unable to distinguish between different levels of performance and only registers whether a person is fully functional or not for each item. Aims: The EHDN Functional Working Group piloted the use of an expanded response scale for the items of the UHDRS Total Functional Assessment. Methods: Twenty-one people with a genetic diagnosis of HD took part in this study. The participants were consecutive patients presenting at clinic and represented a mix of stages, ranging from premanifest to the later stage HD. We expanded the UHDRS Total Functional Assessment original binary response scale with a five-point frequency scale. All patients were seen twice in the one appointment, and assessed using the original scale first, and using the expanded scale later on with a different assessor. Results: The percentage occurrence of endorsement of each score from the 25 item scale from all 21 patients was compared for the original response scale scores and expanded response scale. This showed that intermediate (new) response options in the expanded scale accounted for approximately 20% of responses when the expanded scale was used, indicating that patients and interviewer clearly do use these options when presented. Qualitative comments suggested that for some patients, these options were useful in fully depicting a patient's level of function. The total scores for the original and expanded response scales were also correlated with the UHDRS motor score and UHDRS Total Functional Capacity score. Compared to the TFA scores from the original scale, the expanded scale scores showed greater correlations with both UHDRS motor and UHDRS Total Functional Capacity scores. Conclusions: An initial attempt to expand the response options for the UHDRS TFA, without changing the existing question items looks promising in terms of better capturing functional information. The expanded TFA also appeared to better reflect HD stage in terms of UHDRS motor and UHDRS Total Functional Capacity scores.